Linking Multiscalar Fisheries Using Metacoupling Models - Carlson, Andrew K.; Rubenstein, Daniel I.; Levin, Simon A. (Frontiers in Marine Science, 2020)
Marine fisheries are social-ecological systems important for human health and livelihoods. However, research approaches that consider human-nature interactions within as well as between adjacent and distant fisheries are scarce. As such, we measured and modeled marine fisheries catches at local and regional scales over 65 years (1950–2014), assessed cross-scalar interactions among fishing types (artisanal, subsistence, industrial, recreational), and predicted future catches using the metacoupling framework, a new approach for evaluating human-nature interactions within and across adjacent and distant fisheries (metacouplings). Across taxa examined (mahi-mahi [Coryphaena hippurus], Atlantic bluefin tuna [Thunnus thynnus], cods [Gadidae]), 75% of catches (8.5 million metric tons [MMT]) were made by nations in their own exclusive economic zones (EEZs; Type 1 fishing). However, catches in adjacent EEZs (Type 2 fishing, 1.0 MMT) and distant EEZs and the high seas (Type 3 fishing, 1.9 MMT) increased substantially for all taxa at certain times, becoming consistently important for tuna and cods after 1980. Moreover, Types 1–3 fishing interacted in ways that affect humans differentially across fisheries. For instance, tuna artisanal and subsistence catches (Type 1) decreased with increasing Type 2 and Type 3 industrial fishing, respectively. Cod subsistence catches declined with increasing Type 2/3 industrial fishing and Type 1 artisanal fishing, whereas fishing-type interactions were largely positive for mahi-mahi, causing catches to increase across sectors. Overall, metacouplings affect humans in positive and negative ways that vary across scales and fisheries systems, galvanizing the need for metacoupling-informed fisheries research, policy, and management programs.